Policy paradigms and path dependence: the endogenous roots of institutional displacement and drift in India - Mukherji, Rahul; Zarhani, Seyed Hossein (Global public policy and governance, 2021)
This paper demonstrates the impact of path-dependent policy paradigms on institutional progression. This could involve institutional journeys from democracy to authoritarianism, from federalism to centralization, and vice versa. First, we posit that policy ideas are more important than material interests for the evolution of historical paths. Second, the sequence of path construction is equally important. This paper points to the significance of policy ideas for the construction of two sequences—a layering-tipping-displacement path—and a path of institutional drift. Our case work describes how the layered evolution of ideas led to a tipping point that transformed a public sector-driven regime into a private sector oriented one in 1991, thereby unleashing India’s rapid economic growth. The causal mechanism suggests that layering leading to a tipping point that displaces the old paradigm can reveal why overtly abrupt change may result from gradual endogenous processes. This is a largely unexplored causal mechanism in comparative politics. The paper also demonstrates that an ideational drift away from the federalising frame evolved since 2014. It has resulted in famishing the Indian sub-national states for development expenditure, especially at the time of COVID-19. Scholars have suggested the causal logic behind conversion, drift, layering and displacement largely based on material factors. This paper connects ideas embedded in policy paradigms with two of these paths.